Associations of dynamic driving pressure and mechanical power with postoperative pulmonary complications–posthoc analysis of two randomised clinical trials in open abdominal surgery. (May 2022) - Schuijt, Michiel T.U.; Hol, Liselotte; Nijbroek, Sunny G.; Ahuja, Sanchit; van Meenen, David; Mazzinari, Guido; Hemmes, Sabrine; Bluth, Thomas; Ball, Lorenzo; Gama–de Abreu, Marcelo; Pelosi, Paolo; Schultz, Marcus J.; et al.
Summary: Background: While an association of the intraoperative driving pressure with postoperative pulmonary complications has been described before, it is uncertain whether the intraoperative mechanical power is associated with postoperative pulmonary complications. Methods: Posthoc analysis of two international, multicentre randomised clinical trials (ISRCTN70332574 and NCT02148692) conducted between 2011–2013 and 2014–2018, in patients undergoing open abdominal surgery comparing the effect of two different positive end–expiratory pressure (PEEP) levels on postoperative pulmonary complications. Time–weighted average dynamic driving pressure and mechanical power were calculated for individual patients. A multivariable logistic regression model adjusted for confounders was used to assess the independent associations of driving pressure and mechanical power with the occurrence of a composite of postoperative pulmonary complications, the primary endpoint of this posthoc analysis. Findings: In 1191 patients included, postoperative pulmonary complications occurrence was 35.9%. Median time–weighted average driving pressure and mechanical power were 14·0 [11·0–17·0] cmH2 O, and 7·6 [5·1–10·0] J/min, respectively. While driving pressure was not independently associated with postoperative pulmonary complications (odds ratio, 1·06 [95% CI 0·88–1·28]; p =0.534), the mechanical power had an independent association with the occurrence of postoperative pulmonary complications (odds ratio, 1·28 [95% CI 1·05–1·57]; p =0.016). These findings were independent of body mass index or the level of PEEP used, i.e., independent of the randomisation arm. Interpretation: In this merged cohort of surgery patients, higher intraoperative mechanical power was independently associated with postoperative pulmonary complications. Mechanical power could serve as a summary ventilatory biomarker for the risk for postoperative pulmonary complications in these patients, but our findings need confirmation in other, preferably prospective studies. Funding: The two original studies were supported by unrestricted grants from the European Society of Anaesthesiology and the Amsterdam University Medical Centers, Location AMC. For this current analysis, no additional funding was requested. The funding sources had neither a role in the design, collection of data, statistical analysis, interpretation of data, writing of the report, nor in the decision to submit the paper for publication.